Kajian Penghasilan Dan Komposisi Enap Cemar Dari Loji-Loji Olahan Air Di Negeri Perak Dan Kesesuaian Sebagai Bahan Binaan - Shuib, Nor Lila (2003)
The objectives of the study are to estimate the quantity of sludge produced, to identify the characteristics of raw water and sludge, and to identify the composition of elements in the sludge with the possibility of using it as a useful material in the future. In order to meet these objectives, several tests were conducted on raw water samples and sludges. These include test on pH, turbidity, total suspended solids, moisture content, specific gravity and composition of elements in the sludge.